Dynamic behavior of microcapsule-based self-healing concrete subjected to impact loading. (27th September 2021) - Huang, Yijiao; Wang, Xianfeng; Sheng, Min; Qin, Dawei; Ren, Jun; Zhou, Xiaoqing; Zhu, Jihua; Xing, Feng
Highlights: Dynamic behavior of microcapsule-based self-healing concrete was studied with SHPB. Substantial differences in the post-test damage patterns are observed. The strain-rate sensitivity threshold occurs at 25.7 s −1 for the materials. The empirical DIF relations are proposed based on the test results. Abstract: This paper reports an experimental investigation on the dynamic behavior of microcapsule-based self-healing concrete subjected to impact loading. Dynamic impact tests were carried out using a Ø40-mm split Hopkinson pressure bar (SHPB) apparatus. The strain rate ranged from 30 s −1 to 200 s −1, and self-healing concrete with different mass fractions of microcapsules (0%, 2%, 5%, and 8%) was prepared. The effects of microcapsules on the dynamic compressive properties were investigated and compared with those observed in quasi-static tests. The strain rate effects on dynamic strength, failure pattern, and energy absorption were also investigated. The results show that the dynamic mechanical properties of the self-healing concrete exhibit strong strain-rate dependency. The dynamic compressive strength and strain energy density increase with increasing strain rate. Substantial differences in the post-test damage patterns are observed between the control and experimental groups. The dynamic increase factor (DIF) of the self-healing concrete increases with the strain rate in an approximately logarithmic manner, and the strain-rate sensitivity threshold occurs at 25.7 s −1 . Empirical DIF relations are proposed based on the test results for predicting the material behavior of structures subjected to static and impact loading.